2022
DOI: 10.3390/agronomy12051217
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Agronomic Evaluation of Drought Tolerance in Ten Egyptian Wheat (Triticum aestivum L.) Cultivars

Abstract: This investigation was carried out for genetic characterization and determination of drought tolerance of ten Egyptian cultivars of wheat (Triticum aestivum L.), namely Misr 1, Misr 2, Gemmiza 9, Gemmiza 10, Gemmiza 11, Gemmiza 12, Shandawel 1, Giza 168, Giza 171, and Sids 14. These cultivars were grown in two winter seasons: 2018/2019 and 2019/2020 at the experimental farm Fac. of Agric., Suez Canal Univ., Ismailia, Egypt, under two watering regimes: normal (100%) and stress (50% FC) conditions. Six agronomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…The amplification of unique SCoT bands in drought-tolerant genotypes was also recorded by Shaban et al (2022). In harmony with our results, Emam et al (2022) amplified unique SCoT bands with drought tolerance. Therefore, SCoT can be applied to differentiate between different drought stress tolerances according to markers associated with new alleles for this trait in given selected genotypes.…”
Section: Scot Markers For Drought Tolerancesupporting
confidence: 89%
“…The amplification of unique SCoT bands in drought-tolerant genotypes was also recorded by Shaban et al (2022). In harmony with our results, Emam et al (2022) amplified unique SCoT bands with drought tolerance. Therefore, SCoT can be applied to differentiate between different drought stress tolerances according to markers associated with new alleles for this trait in given selected genotypes.…”
Section: Scot Markers For Drought Tolerancesupporting
confidence: 89%
“…Further research is required to elucidate the mechanisms by which PGPR regulate water and to optimize their application in agriculture. PGPR have been found to have a significant influence on the plants relative water content (El-Mageed et al, 2022). In conclusion, endophytic and rhizobacterial maintain the better root growth that can ensure the better water uptake to counter the toxic effects of drought.…”
Section: Use Of Molecular Markers To Identify Drought Signaling Genesmentioning
confidence: 90%
“…Classical breeding programs can be utilized to identify and incorporate drought tolerance mechanisms in crops that are suitable for water-limited regions (Han et al, 2020). In a study conducted by Emam et al (2022) the consequence of drought and irrigation on productivity and yield-related traits of wheat cultivars was assessed. The findings indicated that wheat genotypes exhibiting favorable characteristics associated with grain production could be selected for both irrigated and water-stressed environments.…”
Section: Physiological Responsesmentioning
confidence: 99%
“…Sravanthi et al (2022) identified two drought-tolerant genotypes which had stable performance under both stress and irrigated conditions. Screening diverse genotypes for drought tolerance under different drought conditions was also conducted with the use of different crops such as cowpea (Fatokun et al, 2012), sorghum (Naoura et al, 2019), peanut (Abadya et al, 2021), and wheat (Emam et al, 2022), resulting in selection of higher yielding genetic resources. Therefore, assessment of diverse germplasm collections can be sourced for drought tolerance and agro-quality traits to select unique lines for breeding.…”
Section: Core Ideasmentioning
confidence: 99%